2014
DOI: 10.5958/0974-0279.2014.00006.8
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Participation in Informal Groundwater Market in Hard Rock Areas of Peninsular India

Abstract: This paper has analysed the factors that influence farmers' participation in the informal groundwater market using the Cragg's double hurdle model. For the study, primary data from 171 groundwater farmers belonging to the Eastern Dry Zone of Karnataka were used. The empirical results have shown that agricultural credit and farmers having failed wells positively influence farmers' probability of water buying. With increasing water cost, the farmers are more likely to purchase or sell water and the quantity of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…When a farmer uses irrigation to a higher proportion of his or her own land, he or she needs more water for the farm and therefore sells less water on the market. This result is consistent with Manjunatha et al (2014), which found a positive effect of water sales revenues on the level of water sold in India.…”
Section: Factors Affecting Water Selling and The Extent Of Water Sell...supporting
confidence: 91%
See 3 more Smart Citations
“…When a farmer uses irrigation to a higher proportion of his or her own land, he or she needs more water for the farm and therefore sells less water on the market. This result is consistent with Manjunatha et al (2014), which found a positive effect of water sales revenues on the level of water sold in India.…”
Section: Factors Affecting Water Selling and The Extent Of Water Sell...supporting
confidence: 91%
“…These non-functioning wells represent sunk costs in agriculture and have contributed to an increase in water costs. As a result, water buyers prefer to buy water rather than invest in additional tubewells, because such investments on the same land are risky and huge (Manjunatha et al, 2014). reported similar findings in the water markets of the Eastern Dry Zone of Karnataka, India.…”
Section: Factors Influencing Water Buying and Level Of Water Buyingmentioning
confidence: 72%
See 2 more Smart Citations
“…The positive sign associated with the variable wage work argues that farmers participating in wage-earning activities are less likely to choose surface water as a source of irrigation over groundwater. This contradicts with Manjunatha et al (2014), who observed farmers with significant income from non-crop activities, such as dairy, have less interest in farming and ultimately practice less intensive farming using surface water as the cost is relatively lower. Wage-earning activities are stressful, laborious, and uncertain, and less gainful.…”
mentioning
confidence: 73%